Empowerment of elementary school teachers on Psychosocial Structured Activities (PSSA) - Anestasia Pangestu Mei Tyas; Amellia Mardhika; Arina Qona'ah; Joko Susanto; Ilkafah Ilkafah (University of Merdeka Malang, 2023)
Natural disasters (floods) can cause psychological impacts and potential public health hazards. Children carrying out daily activities will be disturbed, including learning, fear, and remembering the flood under normal conditions. Children need mental health and psychosocial support, which are essential in creating and supporting states that allow optimal growth and welfare of children in disaster situations. Deket Sub-district, one of the sub-districts in Lamongan Regency, is a frequent flood. Sidomulyo Village has the highest flood height, with water levels between 15 to 37 centimeters in 2022. SDN Sidomulyo 1 is one of the schools affected by this annual flood. This activity aims to increase elementary school teachers' knowledge and skills in providing Psychosocial Structured Activities (PSSA) through empowering elementary school teachers. The method used is the first stage: training elementary school teachers, the second stage: assisting elementary school teachers in carrying out PSSA for elementary school students, and the third stage: is evaluation and follow-up plans. The teachers and students were enthusiastic and active in participating in the various stages of the activity. There is an effect of training PSSA on the level of teacher knowledge (p = 0.014), and all teachers have good skills after being given training and mentoring.